Exploring the impact of health & fitness on successful aging amongst Singapore's golden generation - Muhammad Hafiz Adnan (2018)
Singapore will be classified as a ‘Super-Aged’ Nation by 2030, with seniors constituting 25 per cent of the population. This large demographic shift brings about many challenges; one of which is getting seniors to maintain their health as they age, lest they get overburdened by illness in their twilight years. The growing senior population will also place a significant strain on Singapore’s healthcare sector. Thus this paper attempted to examine the impact of fitness and exercise on successful aging in seniors, and if causality existed, whether it is positive or negative. Utilizing a quantitative survey, this study identified some positive causality; but it was insufficient for achieving complete, successful aging. The paper ultimately recommended complimentary approaches that synergise with fitness and exercise, allowing seniors to stay active and healthy, and contribute to the workforce past their retirement years.